(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The aim of the research is to clarify the measurement of the impact regarding financial value of human resources on investors’ decisions by considering that the human element is one of the assets of the company. Therefore, a set of criteria must be available to determine the applicability of these standards in the human resource because it has an effective role in the success for the company. Is to measure the value of human resources in a financial format according to the first two methods depends on the value and the second depends on the cost. In order to achieve the objectives of the study, a questionnaire was designed to survey the views of a number of employees of the General Company for Leather Industries in order to arrive at the hypothesis that there is a relation of statistical significance to the impact of the financial value of human resources on investors’ decisions and in the analysis of the questionnaires, it was concluded that there is a real moral effect on the financial value of resources On investor decisions